Telekommunikation in Britisch-Indien (ca. 1850–1930).: Ein globalgeschichtliches Paradigma - Mann, Michael (Comparativ, 2009)
So far, the history of the telegraph has been told from a trans-Atlantic perspective. Likewise, the history of the telegraph has been written as a history of technological invention and scientific progress measurable in the mileage of underwater cables. However, the social consequences of the new communication medium have been neglected almost completely. Taking South-Asia (British India) into consideration it becomes evident that the history of the telegraph is by far more complex than hitherto assumed. In the first place contemporary telegraphic connection across the Atlantic was as important as connecting British India with the centre of the British Empire, i.e. London, simply for economic and financial reasons. Secondly, the invention of a practicable telegraphic system took place in the USA, in Great Britain and British India simultaneously during the 1830s. In British India one of the world’s largest telegraph system was constructed outside Europe and the USA. Thirdly, completing the world-wide network of telegraph systems at the beginning of the twentieth century caused massive tariff-competition among the globally acting telegraph cartells leading to strikes in the US and British India which had enormous social consequences for the telegraph personnel. Fourthly, as in Europe and the USA, the possibility to telegraphically transmit information created new forms of news, journalism and newspaper-layouts in British India (as well as in other parts of the world) and helped to establish an all-India public sphere by the 1920s.